SYNTHESIS AND INFRARED STUDY OF SOME SULFATO TRIORGANOTIN DERIVATIVES AND ADDUCTS - DAOUDA NDOYE; LIBASSE DIOP (Scientific Study & Research: Chemistry & Chemical Engineering, Biotechnology, Food Industry)
On allowing ethylenediammonium sulfate or Me4NSO4H to react with SnPh3Cl or SnBu2Cl2 in ethanolic media in specific ratios the three sulfato complexes were obtained and their infrared study carried out. The molecular structures of these compounds have been proposed on the basis of the infrared data. Discrete structures are suggested: the sulfate anion is tetradentate in two of them and monodentate in the other, the tin center being in a trigonal bipyramidal environment in all the structures. When the ethylenediammonium ion is involved through hydrogen bonds, dimeric structures may be obtained.